Polysaccharides From the Roots of Millettia Speciosa Champ Modulate Gut Health and Ameliorate Cyclophosphamide-Induced Intestinal Injury and Immunosuppression - Chen, Xiaogang; Sun, Wenjing; Xu, Baichang; Wu, Enyun; Cui, Yao; Hao, Kaiyuan; Zhang, Geyin; Zhou, Congcong; Xu, Yanping; Li, Jiang; Si, Hongbin (Frontiers in Immunology, 2021)
Cyclophosphamide (CTX), a common anticancer drug, can cause a variety of side effects such as immunosuppression and intestinal mucosal injury. Polysaccharides are the major bioactive components of the roots of Millettia Speciosa Champ and have gained attention for their immunomodulatory activity. This study aimed to evaluate the immunomodulatory effect of Millettia Speciosa Champ polysaccharide (MSCP) on CTX-induced mice and the possible mechanism. The results showed that MSCP attenuated the CTX-induced decrease in body weight and immune organ indices in mice, and promoted the production of immune-related cytokines (IL-2, IL-4, IL-10, TNF-α and IgG). Meanwhile, MSCP restored intestinal morphology, increased the ratio of villus height/crypt depth (V/C), and improved the quantity of goblet cells and mucins expression. At the mRNA level, MSCP activated the TLRs/MyD88/NF-κB p65 pathway and enhanced the expression of genes related to intestinal mucosal integrity (Occludin1, Claudin1 and MUC-2). In addition, MSCP as a prebiotic improved microbial community diversity, regulated the relative abundance of dominant microbiota from the phylum level to the genus level, restored CTX-induced gut microbial dysbiosis, and promoted short-chain fatty acid production in mice. The present results indicated that MSCP might modulate the immune response depending on enhancing intestinal health, suggesting that MSCP holds promise as a promising immunostimulants in functional foods and drugs.